Tandem Observations of Nighttime Mid‐Latitude Topside Ionospheric Perturbations - Hosub Song; Jaeheung Park; Yaqi Jin; Yuichi Otsuka; Stephan Buchert; Jaejin Lee; Yu Yi (Space Weather, 2023)
Abstract Nighttime medium‐scale traveling ionospheric disturbances (MSTIDs) have been generally observed by ground‐based instruments. However, they provide 2‐dimensional images over only a limited field of view and are not distributed globally. The ground‐based observations reported that MSTID wavefronts exhibit backward‐C shapes virtually straddling the dip equator. In situ plasma density measurements onboard individual satellites could overcome the limited coverage of ground‐based MSTID observations. But, most of those spacecrafts could obtain only 1‐dimensional profiles of plasma density, which leaves uncertain whether the observed perturbations generally have the characteristic directivity of MSTIDs. This paper addresses this knowledge gap by statistically investigating nighttime perturbations in the mid‐latitude topside ionosphere observed by tandem satellites, Swarm A and C. We cross‐correlate the plasma density profiles observed by Swarm A and C. The correlation coefficient tends to increase as the two spacecraft move closer, allowing us to derive the disturbances' directivity whenever the Swarm A and C observations are correlated significantly. The directivity statistics agree well with the backward‐C shape. Furthermore, the wavefront directions have clear dependence on magnetic latitudes while they are not as well aligned with local time, which is also consistent with previous reports on nighttime MSTIDs using ground‐based observations and computer simulations. Additionally, we demonstrate that the nighttime MSTIDs can increase the topside Rate Of Total electron content Index above Swarm. All the above‐mentioned results support that the nighttime mid‐latitude perturbations observed by Swarm can be identified as MSTIDs on the whole, which is the most important finding of this paper.